Development of empirical vulnerability curves of masonry building types in Bohol using methods in the global earthquake model (GEM) - Licerio, Arthel Rae T.; Tingatinga, Eric Augustus J.; Longalong, Romeo Eliezer U. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The GEM is a public-private partnership that aims to create a standardized way of assessing seismic risk and to assess risk, vulnerability curves are developed. Vulnerability curve is an expression of seismic loss as a function of an intensity measure type. Using methods in GEM, empirical vulnerability curves are developed for masonry building types in Bohol. The data gathered was from the Bohol Earthquake 2013. The intensity measure used for the study is a seismic intensity scale based on the intensity scale of PHlVOLCS. The statistical model and model fitting technique used to develop the vulnerability curves are the Generalised Linear Model and the Maximum Likelihood Method, respectively. The models developed are based on the assessed quality of the available data given by PHIVOLCS. The models' goodness of fit was identified and the optimum model was reported to be the empirical vulnerability curve. The equivalent curve of the developed empirical vulnerability curves have the following parameters: 1. CHB: mean - 7.93, standard deviation - 0.077 2. MWS: mean - 7.98, standard deviation - 0.080.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Earthquake hazard analysis; Concrete masonry